Job satisfaction of IT professionals in Poland: does business competence matter? - Kowal, Jolanta; Roztocki, Narcyz (Journal of Business Economics and Management, 2015)
This paper examines the effects of business competence on the job satisfaction of Information Technology (IT) professionals in Poland. The necessary data is collected from a survey conducted among 391 IT professionals working in various companies in Poland. The results of the analysis indicate that business competence, in general, positively affects the job satisfaction of IT professionals in transition economies. However, business competence seems to have mixed effects on various aspects of job satisfaction. Although business competence affects satisfaction with co-workers, supervision and work itself, the surveyed IT professionals feel that business competence does not have any substantial effect on their salary level and professional promotions. The theoretical implication of this study is that systematic development of human capital by building business competence will have positive effects on the job satisfaction of IT professionals in transition economies. This paper also has a practical implication for managers in transition economies seeking improvements in productivity as it may help them to devise a compensation and promotion system that would better account for competency in their employees.